2012
DOI: 10.1038/nn.3215
|View full text |Cite
|
Sign up to set email alerts
|

Path integration: how the head direction signal maintains and corrects spatial orientation

Abstract: Head direction (HD) cells have frequently been regarded as an internal “compass” that can be used for navigation, although there is little evidence showing a link between their activity and spatial behaviour. In a navigational task requiring the use of internal cues to return to a home base location without vision (path integration), we found a robust correlation between HD cell activity and the rat's heading error in their homing behaviour. Furthermore, we observed two different correction processes that anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 51 publications
(59 reference statements)
5
98
1
1
Order By: Relevance
“…Although we did not combine all of our experimental techniques into a single unified experiment (due to the technical difficulty of simultaneously implementing electrophysiology, optogenetics, and trained navigational behavior), this study provides additional evidence of a causal relationship between HD cell firing and behavior. This additional evidence critically supplements and expands upon previous studies that have found correlational evidence of this relationship [11][12][13][14][15]. Specifically, this study is the first one to directly and selectively manipulate HD cell firing and subsequently show that this manipulation has a significant effect on behavioral performance.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Although we did not combine all of our experimental techniques into a single unified experiment (due to the technical difficulty of simultaneously implementing electrophysiology, optogenetics, and trained navigational behavior), this study provides additional evidence of a causal relationship between HD cell firing and behavior. This additional evidence critically supplements and expands upon previous studies that have found correlational evidence of this relationship [11][12][13][14][15]. Specifically, this study is the first one to directly and selectively manipulate HD cell firing and subsequently show that this manipulation has a significant effect on behavioral performance.…”
Section: Discussionsupporting
confidence: 74%
“…The results from these studies have been mixed; different studies have shown either correlation or lack of correlation between HD cells and spatial responding depending on the behavior being tested [11,12,13]. More recently, two studies have had success demonstrating a significant correlation between HD cells and navigation in the form of homing behavior [14,15]. However, one limitation of these experiments is that they did not manipulate neural circuits in a way that would allow them to conclude that there is a causal relationship between HD cell firing and navigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results imply a common solution for the interaction of path integration and landmarks in human and animal navigation (Zhao & Warren, 2015). Specifically, visual landmarks reset the path integrator by reorienting the head direction cell system, the grid cell system, and the directional coordinates of the place cell system (Knierim & Hamilton, 2011;Valerio & Taube, 2012;Yoder et al, 2011).…”
Section: Comparison To Animal Navigationmentioning
confidence: 72%
“…Because path integration drifts and error accumulates rapidly (e.g., Loomis et al, 1993), a navigator can take an environmental 'fix' on visual landmarks and re-initialize the path integrator, thereby facilitating reorientation and selflocalization (Etienne & Jeffery, 2004;Etienne, Maurer, Boulens, Levy, & Rowe, 2004;Valerio & Taube, 2012; see also Knierim & Hamilton, 2011). Covertly shifting a visual beacon not only captures an animal's homing behavior, but also induces a corresponding shift in the spatial tuning of underlying neural mechanisms (e.g., place cells, head direction cells, and grid cells; Hafting et al, 2005;Knierim, Kudrimoti, & McNaughton, 1998;Taube et al, 1990).…”
Section: Interaction Between Path Integration and Landmark Navigationmentioning
confidence: 99%